Origin and technology of the Georgian brick at Fade Mansion, Dublin, built c. 1728 - Pavia, Sara (My University, 2021)
This paper studies the provenance and firing technol- ogy of the Fade Mansion brick. The microstructure was studied with scanning electron microscopy (SEM), mineral associations and transformation were deter- mined with X-ray diffraction (XRD) and petrographic analyses. The results evidenced that the bricks were made with a decalcified, silica-based clay of glacio-flu- vial origin, gathered locally. This agrees with the posi- tion of the Mansion on a terrace of the River Liffey, and with previous research on historic bricks made with boulder clay. They were fired in kilns in an oxidising atmosphere. The rubbers at window heads reached lower temperatures which resulted in low vitrification, leading to weathering. Initial vitrification structures generally concur with the occurrence of clay miner- als, indicating temperatures of c. 800°C. Continuous vitrification is associated to the disappearance of clay minerals, the sintering of hematite and/or high-tem- perature phases and mica transformation, indicating a wide temperature range >950-1200°C, which agrees with the inconsistent brick properties.
PUBLISHED
Keywords: Ceramic brick; Firing temperature; Boulder clay; Non-calcareous raw-material; Making Ireland; Nanoscience & Materials